Content-Length: 50603 | pFad | http://citizendium.org/wiki/Talk:Ackermann_function
A ( m , n ) = { n + 1 if m = 0 A ( m − 1 , 1 ) if m > 0 and n = 0 A ( m − 1 , A ( m , n − 1 ) ) if m > 0 and n > 0. {\displaystyle A(m,n)={\begin{cases}n+1&{\mbox{if }}m=0\\A(m-1,1)&{\mbox{if }}m>0{\mbox{ and }}n=0\\A(m-1,A(m,n-1))&{\mbox{if }}m>0{\mbox{ and }}n>0.\end{cases}}} . [d] [e]
Fetched URL: http://citizendium.org/wiki/Talk:Ackermann_function
Alternative Proxies:
Alternative Proxy
pFad Proxy
pFad v3 Proxy
pFad v4 Proxy